Geração de metano em lagoa anaeróbia: um estudo de caso em abatedouro de bovinos - Bohrz, Gabrieli Irrigaray (2010)
This study aims to evaluate the emission of methane (CH4) generated in an anaerobic stabilization pond used to treat wastewater from a cattle slaughterhouse, which is located in Santa Maria, Rio Grande do Sul (RS). In addition to the quantification of CH4 by gas chromatography, it was evaluated the emissions of other greenhouse effect gases (GHG) such as carbon dioxide (CO2) and nitrous oxide (N2O). It was verified the occurrence of two types of fluxes for a release of produced methane: the diffusive, with a daily average equal to 196.0 ± 51 mgCH4m-2h-1; and the ebullient, resulting of the random and sudden release of gases in the form of bubbles with variations between 67.0 and 1295.0 mgCH4m-2h-1. The flow rates values calculated from theoretical models presented significantly higher than the experimental ones, ranging from 387.0 to 410.0 mgCH4m-2h-1, since it was not taken into account the different variables of interference in anaerobic treatment, such as the needs and interactions between bacteria, dilution of the wastewater, and physical-chemical factors. The data revealed a higher production of CO2 (55 vol%) than CH4 (45 vol%) indicating reduction in the production of CH4 and its partial oxidation caused by oscillation in the layer of foam found during the research period. The presence of N2O in the samples indicated the presence of O2 dissolved in the wastewater. The results of this study evidenced that the anaerobic ponds constitute important sources of GHG, emphasizing the importance to control the use of this technology, as a way of mitigating the emission of gaseous compounds into the atmosphere and contribute to reducing the possible negative effects in the environment.